Membrane tube pearling induced by a coupling of osmotic pressure and nanoparticle adhesion. (1st September 2016) - Tian, Falin; Yue, Tongtao; Dong, Wei; Zhang, Xianren
ABSTRACT: In this work, a coarse-grained molecular dynamics simulation method that belongs to the class of dissipative particle dynamics scheme with implicit solvent was used to indicate that adsorption of nanoparticles (NPs) inside a lipid membrane tube and pressure difference across the membrane, e.g. osmotic pressure, cooperatively induce membrane tube pearling. We demonstrate that NP adsorption and aggregation initiate the shape transformation of the lipid tube, and pressure difference provides a driving force for pearling transition. Depending on the dynamic coupling of tube shape transition and NP aggregation in the interior of the tube, different shape transitions via four kinds of pearling pathways are recognised, including pearls on a string (i.e. vesicles are interconnected via either a chain or double-chain of NPs) and tube-to-vesicle transition that is dominated kinetically either by NP-membrane attraction or by pressure difference. Considering the fact that biological membranes are semipermeable and many proteins interact with the membranes, these findings not only provide a mechanism of membrane tube pearling but also demonstrate the importance of osmotic pressure and protein–membrane interaction for many cell activities related to shape transitions of biomembrane. Abstract :